2014
DOI: 10.1002/med.21327
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Proteins and Human Diseases: Pathogenesis, Molecular Mechanisms, and Therapeutic Implications

Abstract: Ribosomes are essential components of the protein synthesis machinery. The process of ribosome biogenesis is well organized and tightly regulated. Recent studies have shown that ribosomal proteins (RPs) have extraribosomal functions that are involved in cell proliferation, differentiation, apoptosis, DNA repair, and other cellular processes. The dysfunction of RPs has been linked to the development and progression of hematological, metabolic, and cardiovascular diseases and cancer. Perturbation of ribosome bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
181
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(183 citation statements)
references
References 374 publications
(1,552 reference statements)
2
181
0
Order By: Relevance
“…Furthermore, patients with two human congenital disorders, Diamond-Blackfan anemia (DBA) and 5q-syndrome, both of which are characterized by deletions or mutations in multiple RP genes, are at higher risk of developing cancers. Taken together, these data strongly suggest a close association of dysfunction of RPs with human tumorigenesis (for recent comprehensive reviews, see (de las Heras-Rubio et al, 2014;Kim et al, 2014;Wang et al, 2015a;Zhou et al, 2012)). In this review, we will focus on the roles of RPs in regulation of cell growth, tumorigenesis and genome integrity, and discuss RPs as potential cancer biomarkers for early diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, patients with two human congenital disorders, Diamond-Blackfan anemia (DBA) and 5q-syndrome, both of which are characterized by deletions or mutations in multiple RP genes, are at higher risk of developing cancers. Taken together, these data strongly suggest a close association of dysfunction of RPs with human tumorigenesis (for recent comprehensive reviews, see (de las Heras-Rubio et al, 2014;Kim et al, 2014;Wang et al, 2015a;Zhou et al, 2012)). In this review, we will focus on the roles of RPs in regulation of cell growth, tumorigenesis and genome integrity, and discuss RPs as potential cancer biomarkers for early diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 58%
“…As suggested by Warner and McIntosh (Warner and McIntosh, 2009), the following criteria must be met to define extraribosomal functions of RPs: (i) interaction with some nonribosomal components of the cell; (ii) the interaction has physiological effects on cellular functions; (iii) the effects occur away from ribosomes; (iv) the effects do not influence protein synthesis. This section will mainly focus on extraribosomal functions of RPs related to a few key cellular processes whose abnormal regulation would lead to tumorigenesis, including apoptosis, cell cycle arrest, cell proliferation, neoplastic transformation, and cell migration and invasion (de las Heras-Rubio et al, 2014;Takada and Kurisaki, 2015;Wang et al, 2015a) (Table 1).…”
Section: The Extraribosomal Functions Of Rpsmentioning
confidence: 99%
“…Extraribosomal function of ribosomal proteins include regulation of gene expression, cell-cycle control, regulation of apoptosis, modulation of DNA repair, regulation of development and differentiation, modulation of cell migration and invasion and regulation of angiogenesis (Wang et al, 2015). Dysfunction of ribosome leads to a condition known as ribosomopathies.…”
Section: Module and Go Enrichment Analysis Of Human Pinmentioning
confidence: 99%
“…High expression of chordin and noggin-1 were detected in early cleavage stage embryos, right after fertilization, indicating maternally packaged chordin and noggin-1 may have unique function in early embryonic development in A. limnaeus (Wagner and Podrabsky 2015). Another study revealed three BMP genes in zebrafish (zBMPs) embryos, BMP-2a, BMP-2b and BMP-4, were expressed in 4, 8,11, and 36 hours after fertilization (Martinez -Barbera, 1997). Human, mouse, Xenopus, and zebrafish BMP-2 and BMP-4 share a conserved sequence motif .…”
Section: Introductionmentioning
confidence: 99%